Discipline Parameter (A Study on Civil Servant’s Work Discipline in Central Java Provincial Court) - Sukoco, Johan Bhimo; Ulya, Fika Ni’matul (Vocational College of Universitas Diponegoro, 2020)
An organization needs to improve its employees’ work discipline. It is important recalling that the objective of organization will be achieved difficultly without the employees’ work discipline. This research studied the work discipline of Civil Servants in Central Java Provincial Court. This study was analyzed using 5 (five) discipline parameters: compliance with work hour and superior’s instruction, compliance with dressing rule, using office facilities well, and working according to the rule (Enceng and Suryarama, 2013). The research method employed in this study was descriptive one with qualitative approach. Primary and secondary data was used in this study. The methods of collecting data used were interview, observation, and documentation study. This study employed an interactive analysis. The result of research showed that parameters of compliance with work hour and superior’s instruction, and compliance with dressing rule such as wearing institution identity card have not been compatible yet with discipline parameters. Meanwhile, the parameter of using office facilities well has been compatible, but archiving aspect has not fulfilled yet the discipline parameter. Parameter of working according to the rule has been compatible, despite some servants asking for permission to get out the office beyond the time limit.